Tinjauan Pustaka: Pengaruh Temperatur Udara keluar Terhadap Proses Penguapan - Salman Alfariz; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The evaporation process is strongly influenced by air temperature, particularly the outlet air temperature, which determines the rate of moisture removal and energy efficiency. This literature review analyzes studies on the impact of outlet air temperature on evaporation performance across various applications, including drying systems, cooling towers, and desalination units. Findings from previous research indicate that higher outlet air temperatures generally increase the evaporation rate due to enhanced vapor pressure differences, yet may reduce overall energy efficiency if not properly controlled. Conversely, optimized airflow and moderate temperature gradients promote stable evaporation with lower energy losses. The reviewed literature highlights the importance of balancing thermal and aerodynamic parameters to achieve effective and sustainable evaporation processes. This review aims to provide a theoretical foundation for improving evaporative system design through precise control of outlet air temperature.